Swimming pool [videorecording (DVD)] - Ozon, François, 1967-; Rampling, Charlotte, 1946-; Sagnier, Ludivine, 1979- (Universal, 2003)
Sarah is a famous British murder mystery author. Tired of London and seeking inspiration for her new novel, she accepts an offer from her publisher to stay at his home in the south of France. Sarah finds that the beautiful country locale and unhurried pace is just the tonic for her - until late one night, when John's sexy and provocative daughter, Julie, unexpectedly arrives. Sarah's English reserve is jarred by Julie's lifestyle. An increasingly unsettling series of events occur that blend a creative process with a possible real-life murder.